2022
DOI: 10.1007/s12144-022-03302-9
|View full text |Cite|
|
Sign up to set email alerts
|

Sex differences in the Dark Triad are sensitive to socioeconomic conditions: the adaptive value of narcissism in the UK, Greece, and China

Abstract: Research has shown that levels of the Dark Triad (i.e., traits of Machiavellianism, narcissism, and psychopathy) vary across sex and age, with males and younger people reporting higher scores. The Dark Triad has also been found to be associated with personal economic status. We investigated whether sex and age differences in the Dark Triad varied across countries of different socioeconomic conditions. We further explored whether the dark traits predicted personal income to different extent across countries. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 41 publications
2
3
0
1
Order By: Relevance
“… 43 Individuals in early adulthood typically exhibit higher levels of Dark Triad traits than those in middle and older ages. 70 As individuals age, their levels of the three Dark Triad traits decrease to varying degrees, 71 which is consistent with the principle of individuals gradually maturing and stabilizing.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“… 43 Individuals in early adulthood typically exhibit higher levels of Dark Triad traits than those in middle and older ages. 70 As individuals age, their levels of the three Dark Triad traits decrease to varying degrees, 71 which is consistent with the principle of individuals gradually maturing and stabilizing.…”
Section: Discussionsupporting
confidence: 72%
“…69 Similar conclusions have been uncovered in studies on Dark Triad, that 43 Individuals in early adulthood typically exhibit higher levels of Dark Triad traits than those in middle and older ages. 70 As individuals age, their levels of the three Dark Triad traits decrease to varying degrees, 71 which is consistent with the principle of individuals gradually maturing and stabilizing. It is identified in the gender difference analysis that higher male psychopathy than female is exhibited in both parents and offspring, which is in line with the outcome of previous studies.…”
Section: Discussionsupporting
confidence: 72%
“…However, not all studies have found men to be higher in the "dark" personality than women, with several even finding the opposite (e.g., Jonason et al, 2020;Luo et al, 2022). Jonason et al (2020) explains the lack of gender differences in the "dark" personality as being due to societal changes and higher gender equality in the countries studied.…”
Section: Discussionmentioning
confidence: 84%
“…Specifically, subjective social class was more strongly correlated with well-being in the United States than in Japan, while objective social class showed the opposite pattern. As another example, research shows that individuals from higher social classes exhibit greater narcissism than those from lower social classes in both Western and Eastern contexts (Aluja et al, 2022), while another dark triad personality trait, Machiavellianism, showed a positive association with social class in the Eastern contexts (e.g., China), but not in Western contexts (e.g., the United Kingdom; Luo et al, 2023).…”
Section: Cross-cultural Perspectivesmentioning
confidence: 99%